PENGARUH RETURN ON ASSET TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Ratna Sari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2022)
The expected achievement of this study is to analyze the effect of Return On Assets on Dividend Payout Ratio (DPR). The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange, as many as 15 companies. The sampling technique used is Purposive Sampling, where this technique selects a certain target group to obtain information. Samples are assigned to specific types of groups that can provide information or because of those groups. The type of data used in this study is quantitative data, in the form of company financial statements which include balance sheets and income statements of Real Estate Companies listed on the IDX for 3 years, namely 2013-2015. The data source is secondary data of Financial Statements to calculate dividend payout ratio originating from representatives of the Indonesia Stock Exchange, namely the Capital Market Information Center (PIPM) in Makassar. The results of the study then the researcher drew a conclusion that partially, this study shows that the observed independent variable has a significant and positive influence on the dependent variable based on the initial hypothesis, with the following details that the Profitability Ratio proxied Return On Asset (X) has a positive and significant effect on the Dividend Payout Ratio.